Supplier Selection Decision Support System On Clothing Convection Using AHP And SAW Methods - Mayonda Mohamad Parli; Anita Diana (Universitas Singaperbangsa Karawang, 2021)
This study discusses the selection of suppliers at a Muslim clothing convection company Iyon Collection in the Jakarta area. Supplier selection is carried out regularly once a year. Some of the problems encountered include the absence of an appropriate method for supplier selection, the absence of a criterion weight value, and no application of a Decision Support System (SPK) for supplier selection that can facilitate the assessment. In addition, the owner of the convection has not yet obtained the required information in the form of a report. Therefore, it is necessary to build an SPK for the assessment of supplier selection. The criteria used include price, quality of materials, distance from supplier to convection, delivery time, discounted prices and supplier service. The method used is the Analytical Hierarchy Process (AHP) to obtain the weight value for each criterion, and the Simple Additive Weighting (SAW) method to find the priority value for ranking each alternative. The purpose of this study is to determine the right assessment method with the right criteria, and determine the value of the weight of the criteria, so as to produce a supplier selection DSS application system that can facilitate the assessment. With the resulting SPK application, the owner also gets the required report information, including supplier data reports, supplier assessment reports and supplier ranking reports. Selection of the right supplier, will be able to provide raw materials for clothing at the right convection on time, to avoid losses in the clothing production process.